The Effect of Earnings Per Share (EPS) and Price Earning Ratio (PER) on Share Price (Case Study of Adro Energy Indonesia Tbk.) - Ibnu Mulyono; Bangun Putra Prasetya (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study plans to decide and demonstrate the impact of Earnings Per Share (EPS) and Value Procuring Proportion (PER) on share costs in Adro Energy Tbk. organizations in 2017-2023. The information utilized in this study is auxiliary information got from different gatherings, to be specific the Indonesia Stock Trade as organization fiscal reports. The example added up to 1 organization. The examination methods completed are by trying old style suspicions, coefficient of assurance (R2), different direct relapse, and speculation tests (F test and t test). In view of the consequences of the examination, it very well may be reasoned that at the same time PES essentially affects the offer cost of Adro Energy Indonesia Tbk organizations recorded on the IDX for the 2017-2023 period, while PER doesn't altogether affect the offer cost of Adro Energy Indonesia Tbk organizations recorded on the IDX for the 2017-2023 period.